BMI ANALYSIS OF OLDER MEMBERS OF A GROUP OF GYMNASTICS (Fiep Bulletin - online, 2016)
In 2025 Brazil will be one of the countries oldest in the world, with a population 13% of seniors. Recalling that, in accordance with the Statute of the Elderly: Law No. 10.741, of October 1, 2003, meant for elderly person or the elderly, individuals with over 60 years of age. Aging is a dynamic and progressive process that make the progressive loss of adaptability of the individual to the environment. Due to much of the epidemiologic evidence supporting a positive effect of an active lifestyle and / or individuals engaging in physical activity and exercise in preventing and minimizing the deleterious effects of aging programs. This study aimed to evaluate the BMI of the elderly participants of a group of fitness of a particular institution of Porto Alegre. Exercise sessions were held 2x (twice) a week lasting one (01) hours during one (01) years. The methodological design characterized by an almost experimental methodology, the type of before and after the study with only one group. Survey participants were in accordance with Resolution 196/96 of the CNS. The sample consisted of 47 elders over 60 years. The results show that the Body Mass Index (BMI) Initial, ie before starting the program (2012), this study found that 0% of the students were within the normal range, however, the vast majority, 72 % presented some kind of abnormality such as overweight (51%) and obese (21%). Regarding the comparative results 2013 Initial and Final 2013 shows that after 5 months of exercise performed 2x per week, BMI scores improved. It was observed that malnutrition continues with 0%, the normal achieved an improvement of 28% to 32%, overweight had decreased from 51% to 47% and obesity continued with the same percentage of 21%.
Keywords: BMI; Fitness; Seniors.